PELAKSANAAN PENGELOLAAN KELAS OLEH GURU BIOLOGI DALAM MENCIPTAKAN DAN MEMELIHARA KONDISI BELAJAR YANG OPTIMAL - Mardhiah, Mardhiah; Eliwatis, Eliwatis; Khaira, Kuntum (Jurnal Pembelajaran MIPA, 2014)
The purpose of this research is find out the applying class management by biology teacher in Junior High School Students 2 Sungayang in creating and keeping learning conditional optimally. The kind of this research was field research. Technique of processing the data was descriptive qualitative, meanwhile technique of Â decking of data was truthworthiness data triangulation by using several sourcer such as interview, observation and dokumentation. Based on the research that have done, it is known that biology teacher in SMPN 2 Sungayang have been able in applying class management in creating and keeping condition learning optimally. It can be seen, because the biology teacher have been able to solve plomblems when learning prosess.Key words: class management, biology teacher